Small business taxes made easy : how to increase your deductions, reduce what you owe, boost your profits, and build a dynasty - Rosenberg, Eva (McGraw Hill-Ascent Audio, 2017)
Axiom Business Book Award Gold Medal Winner Don't be taxed out of business! Know your rights and KEEP MORE OF WHAT YOU EARN It's great to start a business and be your own boss-but with all the taxes you pay, it sometimes feels like you're working for the government. This book teaches you ways to work smarter - not harder! The go-to tax guide for small-business owners is packed with tips for dramatically lowering your taxes. This new edition covers key provisions passed by Congress that will affect your taxes for 2016 through 2020. It includes: * Enhanced checklists * Improved entity comparisons * Updates on valuable business resources and tools * New information about depreciation * Critical home-office information * Need-to-know online business issues * Expanded tips on Tax Notices and audits Small Business Taxes Made Easy covers more than just taxes. It includes business plans, legal tax-cutting tips, and ways to build your dynasty - or develop a smart exit plan (think Venture Capital or IPO). Best of all, you learn how to increase your profits and your cash flow and to ensure your business is a success. You have more rights as a taxpayer than you probably realize, and this unparalleled guide helps you exercise them to the max! Small Business Taxes Made Easy offers easy-to-follow, actionable advice with timeless information. Whatever kind of business you run, this book provides everything you need to hold on to more of the profits you've worked so hard for.